(untitled) (Newcastle upon Tyne, 2012)
Agricultural English is a collection of essays on the English of Agriculture. The approach is a linguistic one: the different aspects of the English used in the field of agriculture (agricultural practices, agricultural systems) and in some fields related to agriculture (agricultural zoology, agri-tourism, biology, botany, ecology, entomology, gastronomy, land measurement, plant pathology, zoology) are analysed from a morphological (combination, derivation), syntactical (nominal phrases, verb...
Keywords: Tiếng Anh,English language; Thuật ngữ và cụm từ,Terms and phrases